Comparative Spectroscopic determination of Heavy Metals Profile of kidney Patients before and after Dialysis and Healthy voluntaries - Iftikhar Hussain Bukhari, Ammara Riffat, Misbah Salam, Iqra Bukhari, Syed Ali Raza Naqvi, Aisha Saddiqa (Journal of Applied Pharmaceutical Science, 2013)
Present study was conducted to quantify and compare the levels of heavy metals in plasma sample of kidney patient before and after dialysis belonging to different areas of Sargodha region. In this study, the level of copper, zinc, cadmium, iron, manganese, lead, chromium and cobalt in plasma sample of Kidney patients has been investigated using atomic absorption spectrophotometer. Heavy metal profile in both normal and diseased subject was determined using dialysis time period and age factor parameters. The mean value of Zn and Fe was found lower in kidney patient as compared to normal subject and reverse was found in case of Pb, Mn, Co and Cr. The heavy metals composition in male patients were found somewhat higher but non-significantly (P>0.05). Age factor revealed that those patients whose age was >30 years have greater values of metals as compared to
Keywords: Heavy metals, Zn, Fe, Atomic absorption, Kidney pati